Peripherally inserted central catheter obstruction in packed red blood cell transfusions in neonates - Maria Gorete de Brito Cunha; Mitzy Tânnia Reichembach Danski; Clélia Mozara Giacomozzi; Andreia Tomazoni; Denise Miyuki Kussahara (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to estimate incidence and free time of peripherally inserted central catheter obstruction in newborns undergoing red blood cell transfusion in the first 24 hours after the procedure. Methods: a longitudinal study, carried out with neonates in Neonatal Intensive Care Unit at a teaching hospital in Paraná, between January and July 2019. The sample consisted of 46 transfusion events performed in neonates through a peripherally inserted central catheter. Analysis performed according to descriptive statistics. Results: thirty-one catheters were analyzed, inserted in 24 neonates, through which 46 red blood cell transfusions were performed. Most neonates were male, gestational age <32 weeks, weight <1,500 grams, hospitalized mainly for prematurity. Among the 31 catheters, one (3.2%) presented obstruction after transfusion. Conclusions: The occurrence of obstructions immediately after transfusion was low and the catheters remained complication free for the next 24 hours.